2022
DOI: 10.31235/osf.io/6adtb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Teacher Burnout Following COVID-19

Abstract: Teachers have faced a multitude of demands over the past two-years and faced new challenges as schools returned in the fall of 2021. Using the Job-Demands Resources model as a framework, the current study identified factors contributing to teacher burnout following the COVID-19 pandemic. To examine predictors of teacher burnout, we collected survey data from 779 teachers across the United States. The analysis included hierarchical regression models including demographics, COVID-19 implementations, and demands/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…For example, teachers' resilience to continue to be involved in teaching and learning processes was found to encompass the people, the socioeconomic system, and the relationships [42]. Similarly, recent studies that focused on teachers' self-efficacy during the pandemic found that teachers' self-efficacy decreased and was associated with overall stress and burnout [14,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, teachers' resilience to continue to be involved in teaching and learning processes was found to encompass the people, the socioeconomic system, and the relationships [42]. Similarly, recent studies that focused on teachers' self-efficacy during the pandemic found that teachers' self-efficacy decreased and was associated with overall stress and burnout [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examine the well-being of Arab teachers in Israel upon schools reopening during the COVID-19 pandemic by employing the Job Demands-Resources Model (JD-R model) [29], given its suitability for examining teaching contexts and teacher's professional well-being [30,31]. The JD-R model suggests that demands and resources (both professional and personal) can predict workers' well-being and performance [32].…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Student behaviour has been identified as a significant contributor to teacher burnout, [7] especially when it comes to managing disruptive or uncooperative students. For Ukrainian EFL teachers, language barriers, cultural differences, or students' lack of motivation to learn English may exacerbate these challenges.…”
Section: Complex Interplay Of Factorsmentioning
confidence: 99%